Automation system for finding parking places - О. Napadii; N. Tsopa; Ye. Batrak (Adaptivni Sistemi Avtomatičnogo Upravlinnâ)
The article examines the prospects for using an automation system to search for parking spaces. This system is aimed at solving the problems that drivers face when searching for available parking spaces, especially in crowded urban areas near residential buildings or shopping centers. A comprehensive literature review and problem analysis revealed existing shortcomings associated with traditional parking search methods: their localized scale and fragmented nature. The article continues the analysis of existing solutions, exploring such well-known mobile applications as ParkMobile and SpotHero, sensor-based and IoT systems, as well as integrated parking technologies. It also provides a comprehensive overview of the technologies on which this type of system is based - GPS, real-time data analysis and sensor networks to simplify parking. The research and analysis identified the innovative potential of automation systems to improve parking management in urban areas. The ability of technology to optimize the use of parking spaces and the entire parking process in general, as well as increase overall urban mobility. The proposed automation system, as an alternative option for searching for parking spaces, has shown high accuracy in predicting the availability of free spaces, providing drivers with real-time information for making informed decisions. A preliminary assessment of the system's operation was carried out based on user feedback and showed good results and further ways to improve the proposed solution. In addition, the system's integration capabilities and user-friendly interface ensure hassle-free and convenient parking in crowded residential areas of the city.